PENGARUH LUAS PANEN DAN HARGA PRODUKSI TERHADAP PRODUKSI TANAMAN JAGUNG KABUPATEN KARO - Quarthano Reavindo; Rita Herawaty Br Bangun (JURNAL AGRICA, 2017)
Corn is a plant that is widely planted in tropical regions due to the way the planting and maintenance is not so difficult and not expensive, in addition to providing food for a large part of people in a nation, corn is also a raw material for the industry. Corn crop farm is one of the food farming business that became an option for farmers in karo District given the natural conditions that apply to plant corn. The purpose of thus research is to know the influence of land and price of production towards the production of corn in karo District in 2015. The analysis data used an analysis of multiple linear regression. The result show that land area affected production meanwhile corn price was not affectedKeywords: broad harvest, production price , production.